2015
DOI: 10.1142/s021812741550042x
|View full text |Cite
|
Sign up to set email alerts
|

Study on Unified Chaotic System-Based Wind Turbine Blade Fault Diagnostic System

Abstract: At present, vibration signals are processed and analyzed mostly in the frequency domain. The spectrum clearly shows the signal structure and the specific characteristic frequency band is analyzed, but the number of calculations required is huge, resulting in delays. Therefore, this study uses the characteristics of a nonlinear system to load the complete vibration signal to the unified chaotic system, applying the dynamic error to analyze the wind turbine vibration signal, and adopting extenics theory for arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Chih-Jer Lin et al adopted [47] the Chen-Lee chaotic system for analysis and took its chaotic attractor as the feature of the ball bearing malfunction recognition, the method combing Chen-Lee chaotic system, and BPNN (Back Propagation Neural Network) had a high identification rate and overall efficiency for the ball bearing malfunction. Ying-Che Kuo et al used [48] the unified chaotic system-based design to study the wind turbine blade fault diagnostic system, Lorenz system, the Lu system, and the Chen system was used to identify which one responds best to this system. The experimental results showed that the unified chaotic system had a significant effect on the vibration signal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Chih-Jer Lin et al adopted [47] the Chen-Lee chaotic system for analysis and took its chaotic attractor as the feature of the ball bearing malfunction recognition, the method combing Chen-Lee chaotic system, and BPNN (Back Propagation Neural Network) had a high identification rate and overall efficiency for the ball bearing malfunction. Ying-Che Kuo et al used [48] the unified chaotic system-based design to study the wind turbine blade fault diagnostic system, Lorenz system, the Lu system, and the Chen system was used to identify which one responds best to this system. The experimental results showed that the unified chaotic system had a significant effect on the vibration signal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For signal analysis, both discrete Fourier [ 17 ] transform and wavelet [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ] were the most frequent analyses used. Over the last few years, chaos systems have been extensively used for diagnosis [ 25 , 26 ] with the fractional-order chaos method giving better diagnostic results, than a simpler chaotic system [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%